The Burden of the Sugar Duty - Taussig, F. W. (Quarterly Journal of Economics, 1909)
The Burden of the Sugar Duty F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 23, Issue 3, May 1909, Pages 548–553, https://doi.org/10.2307/1884780 Published: 01 May 1909